JASA LAYANAN RENOVASI RUMAH OLEH KONTRAKTOR SYARIAH MITRA PROPERTINDO (MI-PRO) MALANG TINJAUAN FATWA DSN MUI NO:09/DSN-MUI/IV/2000 TENTANG PEMBIAYAAN IJARAH - Alifan Muhammad (Journal of Islamic Business Law, 2018)
Sharia Contractors is a new breakthrough in the construction world that attracts many consumers, and most of them are curious about the concept of Shari'a in it. This makes its own benefits for consumers because many of the consumers will indirectly know the types of buildings that fall into the category of syar'i, they also become aware that the concept of sharia can be applied in the world of construction. This study discusses the services of home renovation by sharia contractor Mitra Propertindo Malang which aims to find out how the application of the concept of sharia in construction and review of DSN MUI fatwa no: 09 / DSN-MUI / IV / 2000 on Ijarah financing. The result of this research is, the concept of sharia contractor applied by Mitra Propertindo not only in the form of ijara contract but about all aspects and concepts that become the guidance of Mitra Propertindo. while for the concept of ijarah is in accordance with the fatwa DSN no: 09 / DSN-MUI / IV2000 about ijarah financing because it meets the 4 (four) concepts in the fatwa DSN